Classification of Al-Qur'an Arabic Verses Used Naive Bayes - Syarif Hidayatullah (Jurnal Mantik, 2022)
The development of information globally is very fast, it demands the provision of media information can be enjoyed and felt quickly and precisely. Al-Qur'an as a medium of information in the classical form and contains of science, life, etc. that must be distributed to all human beings orally, in writing, and daily behavior, especially in the field of Islamic laws and aspects of social procedures in Islam. This study applies a classification technique using the method Naïve Bayes which there are three classes or categories namely Sholat (Prayer), Hajj and Wedding. The grouping of these verses takes data from the book of LubaabutTafsir Min Ibn Kathir which later obtained accuracy results 75.52%.